Determinants of safety helmet use among motorcyclists in Kerala, India - Jayadevan Sreedharan; Jayakumary Muttappillymyalil; Binoo Divakaran; Jeesha C Haran (J Inj Violence Res., 2010)
Background: Motorcycles account for a large proportion of road traffic accidents in India and the riders of these vehicles run a high risk of injuries or death. This study aims to explore the determinants of helmet use among motorcyclists in Kerala, India. Methods: A cross-sectional study conducted in Kerala, India, over a period of six months. 309 motorcyclists in Kerala were interviewed for this study using a pretested structured questionnaire. Legislation Results: Among 309 motorcyclists, 80% were less than 40 years of age, and only 24% were Motorcyclist females. Among the total, only 31.4% used a helmet. There was a statistically significant and attitude towards implementing legislative measures. Odds Ratios observed were 5.3 for association between the use of helmet and gender, marital status, drunken driving, use of alcohol female gender compared to male, 4.5 for those with a positive attitude towards the implementation of legislative measures on helmet use, 3.7 for those who were not drunk while driving and 2.3 for unmarried compared to married persons. Conclusions: The study concludes that the determinants associated with the practice of helmet use were gender, drunken driving, marital status and positive attitude towards legal measures.